2016
DOI: 10.1186/s12875-016-0451-x
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of patients with medically unexplained physical symptoms by family physicians: results of a focus group study

Abstract: BackgroundPatients with medically unexplained physical symptoms (MUPS) form a heterogeneous group and frequently attend their family physician (FP). Little is known about how FPs recognize MUPS in their patients. We conducted a focus group study to explore how FPs recognize MUPS and whether they recognize specific subgroups of patients with MUPS. Targeting such subgroups might improve treatment outcomes.MethodsSix focus groups were conducted with in total 29 Dutch FPs. Two researchers independently analysed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 30 publications
2
12
0
2
Order By: Relevance
“…First, regarding the negative effects of biomedical framing of MUS, studies typically report that GPs experience negative emotions when working with MUS, such as uncertainty, fear, frustration and powerlessness [ 2 , 3 , 37 – 41 ]. Yet few studies attempt to understand the cause of the negative emotions on a deeper level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, regarding the negative effects of biomedical framing of MUS, studies typically report that GPs experience negative emotions when working with MUS, such as uncertainty, fear, frustration and powerlessness [ 2 , 3 , 37 – 41 ]. Yet few studies attempt to understand the cause of the negative emotions on a deeper level.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the GPs ‘felt they had the opportunity to ‘know’ such patients better (than other doctors), and build a relationship upon which successful management could be based’ [ 39 ]. GPs are also typically reported to explain MUS by considering the sick person in his or her psychosocial context [ 2 , 3 , 37 , 39 , 40 , 48 50 ]. While the link between this understanding and a form of biopsychosocial framing is rarely explicated, it is certainly indicated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that GPs take various characteristics like multiple MUPS, frequent and long consultations and many referrals into account when recognising MUPS in their patients. 31 Equally, in case of uncertain VVC, GPs should be aware that the increasing number of consultations and comorbidity of MUPS could point to PVD.…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated the matching of exercises to perpetuating factors with the help of eight experienced mental healthcare professionals. Based on a qualitative study describing prototypes of FSS patients (Den Boeft et al, 2016), we created five cases with video vignettes and a short description containing information on patient characteristics. These five prototypical patients varied widely with regard to relevant perpetuating factors.…”
Section: Methods Used For the Development Of The Grip Self-help Intermentioning
confidence: 99%